Information ethics codexes from the perspective of selected information philosophy approaches - Zajda, Tomáš (2023)
The thesis offers an overview of selected intellectual frameworks influencing the field of information ethics (Floridi, Hui, Capurro, and others) as well as their synthesis in the form of a new ethical framework built on concepts such as macroethical and interdisciplinary approach, open community and prudential discussion, hyperreality, infosphere, technodiversity, respect for locality and multitude of epistemologies, practical measures, humans as bearers of responsibility, and more. The thesis also discusses the differences between anthropocentric and non-anthropocentric approaches (Latour, Sokolíčková, and others). The proposed framework is used to analyze contemporary information ethics codexes and to form a new codex of information ethics. Lastly, a critique of ChatGPT is conducted from the perspective of the proposed codex to bring attention to its problematic aspects, such as the use of resources, creation and spreading of misinformation, inadaptibility to localities, or criminal misuse. The thesis aims to promote the susceptibility of organizations and individuals to complex modern issues connected to information, technology, and the environment.